(3bUjOI JTJed Ydi GdNdGa Hjf GdCTYQjI hGdMfajIs - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s
(3ChdgG (B:s
(3GdhQO NOc UjZ ef EfSGf Ce ai GdMOhO TbGFb GdfYeGf s
(3BNQgG (B:s
(3hYdi GHf GdYe hdGHGbhf Cfge GdfLhe GdebJO MjQGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3cJH GdYfhGf hHYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
Keywords: (3GdJhMjO hGdedd hGdfMds